Comparative study of the pure AH Plus sealer and its combination with triple antibiotic paste at different concentrations on Enterococcus faecalis bacteria - Amirreza Mokabberi; Sohyla Aminoroaya Yamini; Arezoo Tahmourespour; Maryam Zare Jahromi (Wolters Kluwer Medknow Publications, 2024)
Background: In this study, the effects of pure AH Plus sealer and its combination with triple antibiotic paste at different concentrations on Enterococcus faecalis bacteria have been investigated. Materials and Methods: This in vitro study was accomplished by the means of a triple antibiotic paste combination (minocycline, metronidazole, and ciprofloxacin) at different concentrations (0%, 1%, 5%, 10%, and 25%) with AH Plus sealer on E. faecalis bacteria. Sealers were set in an incubator for 1 h, 1 day, 3 days, and 7 days, and then 10 µL of bacteria solution was placed on all samples except the negative control group. After drying for 1 h, 250 µL brain-heart infusion broth culture medium was added, and it was cultured in solid media. Direct contact test technique was performed, and the obtained data were analyzed by 1-way ANOVA, 2-way ANOVA, 3-way ANOVA, and post hoc test least significant difference. It should be noted that the data were evaluated at the significance level of P < 0.05. Results: The average of colony-forming unit (CFU)/mL illustrated that there were no significant differences between fresh antibiotic-sealer combination, 1-day set, and 3-day set (P = 0.525), while in sealer with 7-day set, the average of CFU/mL was notably lower than other sets (P < 0.001). The outcomes revealed a considerable variation by passing time and the number of CFU/mL was remarkably reduced (P < 0.05). The data suggested that, by increasing the concentration, the average of CFU/mL was decreased, whereas the average of CFU/mL did not have significant differences in all concentrations of the antibiotic-sealer combination compared to pure sealer (P < 0.05). Conclusion: The concentration of 1% triple antibiotic in combination with root canal sealer may become a crucial factor for inhibiting the growth of remaining bacteria.